2014
DOI: 10.7482/0003-9438-57-017
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of <i>m. longissimus dorsi</i> of Mangalitsa and Moravka pig breeds

Abstract: The objective of this study was to determine the chemical composition and fatty acid content in m. longissimus dorsi (MLD) of two indigenous pig breeds (ML -Swallow-belly Mangalitsa and M -Moravka) reared in free range farm conditions and fed complete mixtures used for commercial meat pig genotypes. The body mass of ML and M pigs at slaughter was,on average, 107.14 and 107.61 kg, respectively. In MLD of M pigs, more total fat was measured compared to ML breed (6.96 % compared to 5.10 %, P<0.05). Protein conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…Results in this study are in accordance with Parunović et al (2013). However, Petrović et al (2014) found lower values of n-6 / n-3 ratio in IMF between indigenous breeds Moravka and Mangalitsa than our results.…”
Section: Traitssupporting
confidence: 74%
See 4 more Smart Citations
“…Results in this study are in accordance with Parunović et al (2013). However, Petrović et al (2014) found lower values of n-6 / n-3 ratio in IMF between indigenous breeds Moravka and Mangalitsa than our results.…”
Section: Traitssupporting
confidence: 74%
“…According to Wood et al (2003) the PF / SF ratio should be increased to above 0.4. Similarly, the British Committee on Medical Aspects of Food and Nutrition Policy (COMA) recommends a PUFA / SFA ratio higher than 0.45 (Petrović et al, 2014). In our study, the PUFA / SFA ratio was from 0.23 to 0.39, which is not in accordance with the recommendations.…”
Section: Traitscontrasting
confidence: 52%
See 3 more Smart Citations